2016
DOI: 10.1038/srep36267
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of top-down cognitive processing for SSVEP-controlled BMI

Abstract: We present a fast and accurate non-invasive brain-machine interface (BMI) based on demodulating steady-state visual evoked potentials (SSVEPs) in electroencephalography (EEG). Our study reports an SSVEP-BMI that, for the first time, decodes primarily based on top-down and not bottom-up visual information processing. The experimental setup presents a grid-shaped flickering line array that the participants observe while intentionally attending to a subset of flickering lines representing the shape of a letter. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Typically, BCI systems based on the modulation of SMR using MI tasks have lower rates of efficiency than other BCI paradigms based on evoked potentials such as event-related potentials (ERP) or steady-state visual potentials (SSVEP) (Chen et al, 2015;Min et al, 2016;Nierhaus et al, 2019). This is because MI-based BCI users normally need to acquire the skill to efficiently perform the MI tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, BCI systems based on the modulation of SMR using MI tasks have lower rates of efficiency than other BCI paradigms based on evoked potentials such as event-related potentials (ERP) or steady-state visual potentials (SSVEP) (Chen et al, 2015;Min et al, 2016;Nierhaus et al, 2019). This is because MI-based BCI users normally need to acquire the skill to efficiently perform the MI tasks.…”
Section: Discussionmentioning
confidence: 99%
“…At present, although higher harmonic responses are an integral part of brain responses, they are not systematically addressed in frequency-tagging research. In many studies, higher harmonic responses are not even reported (e.g., Bekhtereva, Pritschmann, Keil, & Müller, 2018;Min, Dähne, Ahn, Noh, & Müller, 2016;Paulk, Kirszenblat, Zhou, & van Swinderen, 2015;Coia, Jones, Duncan, & Crognale, 2014;Kuś et al, 2013;Cottereau et al, 2011;Wattam-Bell et al, 2010;Di Russo et al, 2007;Müller et al, 2006;Braddick, Birtles, Wattam-Bell, & Atkinson, 2005;Chen, Seth, Gally, & Edelman, 2003;Heinrich & Bach, 2001;Regan & Regan, 1988a;Tononi et al, 1998;Peterzell & Norcia, 1997;Müller, Teder, & Hillyard, 1997;Morgan, Hansen, & Hillyard, 1996, or are extirpated by narrow [band-pass, Gabor, etc. ] filtering, e.g., Davidson, Mithen, Hogendoorn, van Boxtel, & Tsuchiya, 2020;Miskociv & Keil, 2013;Anderson & Müller, 2010;Regan, 1975).…”
Section: Higher Harmonicsmentioning
confidence: 99%
“…Nakanishi et al (2014) implemented a 32-target SSVEP paradigm based on this coding strategy, which was further used to implement a 40-target SSVEP paradigm (Nakanishi et al 2017a). Instead of using a rectangle stimulus array, Min et al (2016) designed an SSVEP paradigm with a grid-shaped line array. Instead of gazing at a single flickering stimulus at a time, Tang et al (2019) designed the multi-focal SSVEPs (mfSSVEPs) paradigm that requires the subject to receive multiple flickers with different frequencies simultaneously.…”
Section: Vision-related Paradigmsmentioning
confidence: 99%